1986
DOI: 10.1111/j.2044-8309.1986.tb00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of gender identity and their implications for gender consciousness

Abstract: Three properties of gender identity-perceived similarity to other women, sense of common fate and centrality of gender to the sense of self-were measured in national surveys of women in the United States. Analyses of their relationships to gender consciousness support the general proposition that these properties of identity are implicated in different ways in collective discontent, criticism of the legitimacy of gender disparities and acceptance of change-oriented collective action. As predicted, the sense of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
161
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(168 citation statements)
references
References 6 publications
4
161
0
3
Order By: Relevance
“…Gardner et al, 2000). Similarly, past research has shown that perceived discrimination against one's group sometimes leads to increased identification with the group (e.g., Dion & Earn, 1975;Gurin & Townsend, 1986;Tajfel & Turner, 1986).…”
Section: Discussionmentioning
confidence: 95%
“…Gardner et al, 2000). Similarly, past research has shown that perceived discrimination against one's group sometimes leads to increased identification with the group (e.g., Dion & Earn, 1975;Gurin & Townsend, 1986;Tajfel & Turner, 1986).…”
Section: Discussionmentioning
confidence: 95%
“…In order to assess the extent to which women felt a sense of common fate with other women, participants indicated on a scale ranging from disagree totally (0) to agree totally (10), how much they disagreed or agreed with six statements. To remain consistent with Gurin and Townsend's (1986) generalized two-item measure of common fate, two items assessed a general sense of common fate: "The status of women has nothing to do with my own personal status"; "Realizing the kinds of discrimination women face has led me to believe that I too could face discrimination". While these items were based on Gurin and Townsend's (1986) measure, they were reworded, as the original wording which asks about the impact of the women's movement on one's life was suspected to have less relevance to a university sample in the 1990s.…”
Section: Methodsmentioning
confidence: 99%
“…To remain consistent with Gurin and Townsend's (1986) generalized two-item measure of common fate, two items assessed a general sense of common fate: "The status of women has nothing to do with my own personal status"; "Realizing the kinds of discrimination women face has led me to believe that I too could face discrimination". While these items were based on Gurin and Townsend's (1986) measure, they were reworded, as the original wording which asks about the impact of the women's movement on one's life was suspected to have less relevance to a university sample in the 1990s. Four additional items were developed to assess the impact of more explicit instances of gender discrimination on individual women.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os itens da Escala de Identificação Social foram constituídos com base: em estudos de Cameron e Lalonde (2001), que desenvolveram uma escala de 28 itens de identificação social, derivados de diferenças de gênero; nos itens de medidas de identidades sociais (Brown et al, 1986;Hinkle et al, 1989) e autoestima coletiva (Luhtanen & Crocker, 1992), bem como, em trabalho anterior sobre a identidade social de mulheres (Gurin & Markus, 1989;Gurin & Townsend, 1986).…”
Section: Modelo Trifatorial Da Identidade Social E Escala De Identifiunclassified